Total Cost of Ownership Based Economic Analysis of Diesel, CNG and Electric Bus Concepts for the Public Transport in Istanbul City - Topal, Orhan; Nakir, Ismail (MDPI, 2018)
As across the world, in Turkey, several studies have been carried out by local government to use sustainable and 100% zero-emission public transport following increased public awareness. Increasing greenhouse gas emissions (GHG) due to transportation systems in the world make it necessary to establish zero-emission sustainable transportation systems in Turkey. In this study, an economic analysis based on actual field data is presented for Istanbul Electricity, Tramway and Tunnel General Management (IETT) to seek the suitability of an electric bus concept for Istanbul conditions. For this purpose, a dynamic model based on the Total Cost of Ownership (TCO) from well to wheel has been proposed for the three groups of transportation, namely diesel, CNG (compressed natural gas) and electric buses. The data source used in the proposed approach is created by performing actual field performance tests for diesel, CNG and electric buses under real Istanbul road, time, and trip conditions. Afterwards, the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PB) methods considering TCO values and updated unit prices are carried out for the investment versus profitability analyses to compare the different public bus concepts. The results show that the electric bus concept with a charging station depot achieving sustainable and zero-emission goals will be the driving force to advance the electric bus concept for Istanbul Public Transport.
Keywords: CNG bus; diesel bus; electric bus; filed performance test; economic analysis; total cost of ownership (TCO); Energy & Fuels